1.1x+4.7=0.6x+4.4

Simple and best practice solution for 1.1x+4.7=0.6x+4.4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.1x+4.7=0.6x+4.4 equation:


Simplifying
1.1x + 4.7 = 0.6x + 4.4

Reorder the terms:
4.7 + 1.1x = 0.6x + 4.4

Reorder the terms:
4.7 + 1.1x = 4.4 + 0.6x

Solving
4.7 + 1.1x = 4.4 + 0.6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.6x' to each side of the equation.
4.7 + 1.1x + -0.6x = 4.4 + 0.6x + -0.6x

Combine like terms: 1.1x + -0.6x = 0.5x
4.7 + 0.5x = 4.4 + 0.6x + -0.6x

Combine like terms: 0.6x + -0.6x = 0.0
4.7 + 0.5x = 4.4 + 0.0
4.7 + 0.5x = 4.4

Add '-4.7' to each side of the equation.
4.7 + -4.7 + 0.5x = 4.4 + -4.7

Combine like terms: 4.7 + -4.7 = 0.0
0.0 + 0.5x = 4.4 + -4.7
0.5x = 4.4 + -4.7

Combine like terms: 4.4 + -4.7 = -0.3
0.5x = -0.3

Divide each side by '0.5'.
x = -0.6

Simplifying
x = -0.6

See similar equations:

| 6x+6=x+26 | | (-75)=y+4y+25 | | 17x+66+11x=-10+x | | 4g+3(-6+4g)=1-9 | | -5(11-2x)-3y=-6 | | 2z+33=17 | | 26y-12=18y+12 | | 6(c-4)=3(s+9) | | 2b+9=188 | | 4(4x-4)+40=9x+3 | | 40.06=8g+3.58 | | 8(5y-3)3.2=x | | -4=-8n+8n | | 45+9x=-14 | | 3x^2(4x+5)= | | 17x+66+11x=-1+x | | 10*.5+8=5*.5+3+3(.5+2) | | -7(9a-4b)= | | 15x+5=-5 | | -3(-n-8)-2(8n+6)=n-8n | | 12y^3-16y^2+4y=0 | | 18a+21= | | (3x-22)=80+x | | 3x+5-2=11-8 | | 8(5x-3)3.2=y | | -(-93)= | | 2x(9-x)= | | 8(n+8)=-8(-5n+1)+4n | | 27m-7m=40 | | 15x=3y+6 | | 8y-62=-y-8 | | 60x-153=9x |

Equations solver categories